2015
DOI: 10.3390/molecules201019277
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Activities of Endolysins Derived From a Mycobacteriophage, BTCU-1

Abstract: Abstract:The high incidence of Mycobacterium infection, notably multidrug-resistant M. tuberculosis infection, has become a significant public health concern worldwide. In this study, we isolate and analyze a mycobacteriophage, BTCU-1, and a foundational study was performed to evaluate the antimycobacterial activity of BTCU-1 and its cloned lytic endolysins. Using Mycobacterium smegmatis as host, a mycobacteriophage, BTCU-1, was isolated from soil in eastern Taiwan. The electron microscopy images revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…As a result, the mycolic acid layer detaches from the cell, rendering vulnerable to osmotic shock and, finally, lysis ( 155 ). Some in vitro assays have been conducted with both mycobacteriophage-derived hydrolases, yielding, in general, promising results that show either growth arrest ( 101 ) or a bactericidal effect ( 103 ), but further research is still required. The mycobacterial endolysins and their therapeutical potential have been recently reviewed ( 156 ).…”
Section: Lysins Against Gram-positive Bacteriamentioning
confidence: 99%
“…As a result, the mycolic acid layer detaches from the cell, rendering vulnerable to osmotic shock and, finally, lysis ( 155 ). Some in vitro assays have been conducted with both mycobacteriophage-derived hydrolases, yielding, in general, promising results that show either growth arrest ( 101 ) or a bactericidal effect ( 103 ), but further research is still required. The mycobacterial endolysins and their therapeutical potential have been recently reviewed ( 156 ).…”
Section: Lysins Against Gram-positive Bacteriamentioning
confidence: 99%
“…Grover et al [186] reported that LysB isolated from the mycobacteriophage Bxz2 has 10-fold higher esterase activity than LysB isolated from the mycobacteriophage Ms6, but that both effectively inhibit the growth of M. smegmatis. Lai et al [187] showed that LysA and LysB isolated from the mycobacteriophage BTCU-1, besides being active against M. smegmatis when administered exogenously, thereby causing severe modifications on the cell wall structure, also inhibited the viability of this mycobacterium growing inside RAW 264.7 macrophages. The promising results of these studies prove that an endolysin approach to treating mycobacterial infections can be applied in the future, also in combination with conventional antibiotics that target the mycobacterial cell wall.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…(Hatfull, 2010). These phages, which are referred to as mycobacteriophages, can kill the bacteria during Recently, one such phage named BTCU-1 that specifically infects Mycobacterium was isolated from a soil sample in Taiwan (Lai et al, 2015). Images of the phage captured using TEM reveal that the phage resembles members of the Siphoviridae family.…”
Section: Introductionmentioning
confidence: 99%